2006
DOI: 10.1292/jvms.68.959
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Neuropeptide Y in Hyperphagia in Human Growth Hormone Transgenic Rats

Abstract: ABSTRACT. We have previously produced human growth hormone (hGH) transgenic (TG) rats that show low circulating levels of both hGH and endogenous rat GH. Although body length of the TG rats is normal, they develop hyperphagia and severe obesity. The present study was undertaken to elucidate the causes of hyperphagia in the TG rats by focusing on temporal changes in plasma ghrelin levels and hypothalamic neuropeptide Y (NPY) contents. In both wild-type (WT) and TG rats, the highest value of plasma ghrelin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…* P <0.05 vs. RW (−) by a Student’s t test.). As reported previously [5,6,7, 9, 11], body weight gain in TG rats was higher than that in WT rats without running wheel access after 14 weeks of age ( P <0.0167, by a Student’s t test and a Bonferroni correction). Running wheel access resulted in decreased body weight gain in both WT and TG rats.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…* P <0.05 vs. RW (−) by a Student’s t test.). As reported previously [5,6,7, 9, 11], body weight gain in TG rats was higher than that in WT rats without running wheel access after 14 weeks of age ( P <0.0167, by a Student’s t test and a Bonferroni correction). Running wheel access resulted in decreased body weight gain in both WT and TG rats.…”
Section: Resultssupporting
confidence: 84%
“…Otsuka Long-Evans Tokushima fatty (OLETF) rats, lacking cholecystokinin receptors, showed temporal decrease of food consumption only in the initial period of wheel access [1], while Zucker fatty rats, which have a leptin receptor missense mutation, did not change their food consumption throughout the experiment [22]. In TG rats, leptin resistance [6], high peripheral ghrelin levels and increased transport of neuropeptide Y (NPY) from the arcuate nucleus (ARC) to paraventricular nucleus (PVN) of the hypothalamus [9] are suspected as the causation of the hyperphagia. Therefore, the different outcomes observed as to the effect of running wheel on food consumption may be attributable to the different causes of hyperphagia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies in rodents suggested a possible mediation of ghrelin action on GH by NPY and that GH may be involved in maintaining feeding [68]. Plasma ghrelin levels are elevated during fasting and suppressed after meal.…”
Section: An Overview Of Hunger-satiety Signals and Autoantibodies mentioning
confidence: 99%